Students' Perceptions of Performance-Based Authentic Assessment in Speaking Recount Text at SMA Swasta Bandung Medan - Neni Afrida Sari Harahap; Yudhistira Aidil Fitrah (Invention: Journal Research and Education Studies, 2026)
This study aims to describe the implementation of performance-based authentic assessment in speaking recount text activities and analyze students' perceptions of this method. The research was conducted at SMA Swasta Bandung Medan, utilizing 10 student respondents as the primary data source. A quantitative descriptive design was applied, employing a survey method for data collection. Data were gathered through an 18-item Likert scale questionnaire distributed via Google Form. The collected data were analyzed utilizing descriptive statistics to calculate mean scores and percentages. The findings establish that storytelling of personal experiences is the dominant type of assessment utilized (100% frequency). Furthermore, students hold a 'Very Positive' overall perception of this assessment method, evidenced by a total mean score of 4.02 out of 5.00. The highest-rated indicator was the authenticity of the assessment (mean 4.17). The implications of this study confirm that performance-based authentic assessment is positively perceived and effectively supports student learning. However, the study also highlights crucial pedagogical and psychological implications, specifically the necessity for educators to actively manage student performance anxiety, mitigate classroom noise, and allocate adequate preparation time.